2010
DOI: 10.1063/1.3503624
|View full text |Cite
|
Sign up to set email alerts
|

Residual parallel Reynolds stress due to turbulence intensity gradient in tokamak plasmas

Abstract: A novel mechanism for driving residual stress in tokamak plasmas based on k ʈ symmetry breaking by the turbulence intensity gradient is proposed. The physics of this mechanism is explained and its connection to the wave kinetic equation and the wave-momentum flux is described. Applications to the H-mode pedestal in particular to internal transport barriers, are discussed. Also, the effect of heat transport on the momentum flux is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 49 publications
4
114
0
Order By: Relevance
“…[9][10][11][12][13][14] Conversion of radial inhomogeneity into hk k i asymmetry requires some symmetry breaking mechanisms. 7,8,[15][16][17][18][19] Role of mean E Â B shearing in symmetry breaking, hence in off-diagonal momentum flux, was identified by many authors. 16,18 Recently, G€ urcan et al showed how the mean E Â B shear can lead to the reflectional symmetry breaking of hk k i in ion temperature gradient (ITG) turbulence, resulting in finite parallel residual stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13][14] Conversion of radial inhomogeneity into hk k i asymmetry requires some symmetry breaking mechanisms. 7,8,[15][16][17][18][19] Role of mean E Â B shearing in symmetry breaking, hence in off-diagonal momentum flux, was identified by many authors. 16,18 Recently, G€ urcan et al showed how the mean E Â B shear can lead to the reflectional symmetry breaking of hk k i in ion temperature gradient (ITG) turbulence, resulting in finite parallel residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…18 Reflectional symmetry breaking of k jj here means generation of eigenmode averaged wave number hk jj i 6 ¼ 0 by symmetry breaking of eigenmode about a rational surface, i.e., by j/j 2 ðxÞ 6 ¼ j/jðÀxÞ. Turbulence intensity gradient can also induce hk k i symmetry breaking, 19 which may be an important driver of the intrinsic torque near the top of a transport barrier where a strong fluctuation intensity gradient is present. The process of hk k i symmetry breaking by E  B shear and/or intensity gradient implies a coupling between intrinsic rotation and transport barrier dynamics, such as internal transport barrier (ITB) formation, which involves steep temperature and/or density gradients (i.e., strong radial inhomogeneity) and the strong E  B shear and/or the fluctuation intensity gradient (i.e., hk k i symmetry breaking).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One residual stress component has been derived to be due to the gradient of the turbulence intensity field I. 10,11 Including this residual stress is only possible in a transport model where the turbulence intensity is accessible, and thus, this constitutes a unique aspect of this model.…”
Section: Turbulence Spreading Transport Modelmentioning
confidence: 99%
“…These ideas focus on the role of "residual stress," P r , that is, the portion of the angular momentum flux that is not proportional to the velocity or to its gradient. 283,284 The divergence of the residual stress constitutes the intrinsic torque. In the enhanced confinement regimes, P r is a function of the temperature gradient.…”
Section: Momentum Transportmentioning
confidence: 99%